PENERAPAN MEDIA PEMBELAJARAN BERBASIS AUGMENTED REALITY UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS VIII PADA MATERI BANGUN RUANG SISI DATAR - S, Sri Wulan; Badu, Syamsu Q.; Takaendengan, Bertu Rianto (JP2M (Jurnal Pendidikan dan Pembelajaran Matematika), 2026)
The limited use of instructional media in teaching the topic of Three-Dimensional Shapes with Flat Surfaces has negatively impacted students' mathematics learning outcomes. This issue became the basis for conducting this study. The purpose of this research is to determine whether the application of Augmented Reality (AR)-based mathematics learning media can improve student learning outcomes on the topic of three-dimensional shapes in Class VIII at SMP Negeri 1 Tilongkabila.During the second semester of the 2024/2025 academic year, a total of 30 students from Class VIII-2 of SMP Negeri 1 Tilongkabila participated in this Classroom Action Research (CAR). Data were collected through observation of teacher and student activities, as well as students’ learning test results. The research procedure included the stages of planning, action implementation, observation, and reflection, carried out over two cycles.The findings of the study showed an increase in teacher activity from 71.69% in Cycle I to 87.91% in Cycle II. Similarly, student activity also improved from 69.29% to 86.71%. The average score of students’ mathematics learning tests rose from 63.33% in Cycle I to 86.66% in Cycle II, with all students achieving scores above the Minimum Mastery Criteria (KKM) of 70.